Early Christian poetry : a collection of essays - Boeft, J. den.; Hilhorst, A. (Vigiliae Christianae, Supplements, 1993)
This collection of essays deals with the rise and development of early Christian poetry, discussing its techniques and its theoretical foundation. The individual papers concern specimina of Hebrew, Syriac, Greek and Latin poetry and study the various and partly conflicting traditions from which it originated. The biblical examples, e.g. of the Psalms, held great authority, but on the other hand it was impossible to break away from the models of classical Greco-Roman poetry, although these were deemed dangerous because of the pagan content and excessive cult of literary art. The book shows how the problems involved were solved in different ways, which justified the use of pagan literary accomplishments for singing the praises of the Lord.